PERHITUNGAN STABILITAS KAPAL PERIKANAN MELALUI PENDEKATAN UKURAN UTAMA DAN KOEFISIEN BENTUK KAPAL - Hutauruk, Ronald Mangasi (Jurnal Perikanan dan Kelautan, 2013)
This research was conducted in December 2012 with tuna longliner as the objectin which designed operated in Bungus Waters, Province of West Sumatera. The objectof the research was the review of previous reseach with optimatized main dimensionnamely LWL = 29,27 m, LPP = 28,14 m, B =6,40 m, H = 3,57 m dan T = 2,87 m. Theaim of this research is to calculate tuna longliner stability by inputting main dimension,form coefficients, and various other additional paramaters. Its value was entered toequations of stability calculation so that resulting a value that will be checked its statustowards stability criterion according to IMO. Calculation result conclude that tunalongliner stability satisfy IMO criterions.